Quality Changes of Tilapia Fish (O. niloticus) by Killing Techniques and Gutting during Low Storage Temperature - Aris Munandar; . Nurjanah; Mala Nurilmala (Jurnal Pengolahan Hasil Perikanan Indonesia, 2009)
Killing and gutting treatment at low storage temperature (0-5 oC) on tilapia fish (O. niloticus) showed significant results on the subjective test (organoleptic) and objectives (TPC/Total Plate Count, pH, and TVB/Total Volatile Base). The A1B2 treatment (dead pricker, gutting) gare the best quality, and this could he maintained for 10 days. Tilapia fish could be consumed up to-10 days because the number of bacteria at the end of the storage prevent reached 9.7x105 colonies/g. TVB value generated at the end of the storage period reached 20.45 mg N/g with some fluctuation of pH value during the storage. The quality of tilapia fish could maintain with the combination of treatment and storage at low temperature (0-5 oC).Keywords: chilling, fish quality, tilapia